Executive secrets : covert action and the presidency - Daugherty, William J., 1947- (Lexington : University Press of Kentucky, 2004)
"A HISTORY BOOK CLUB SELECTION With a Foreword by Mark Bowden, author of Black Hawk Down.
The role of covert action in intelligence and foreign policy -- The "romances" of covert action -- Covert action policy and pitfalls -- The military and peacetime covert action -- The discipline of covert action -- Approval and review of covert action programs in the modern era -- Harry S. Truman -- Dwight D. Eisenhower -- John F. Kennedy and Lyndon B. Johnson -- Richard M. Nixon and Gerald R. Ford -- Jimmy Carter -- Ronald W. Reagan -- George H.W. Bush and William J. Clinton -- Conclusion.
Includes bibliographical references (pages 257-275) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: United States. -- Central Intelligence Agency; États-Unis. -- Central Intelligence Agency; United States. -- Central Intelligence Agency; USA -- Central Intelligence Agency; USA -- Präsident; Intelligence service -- United States -- History -- 20th century; Presidents -- United States -- History -- 20th century; United States -- Foreign relations -- 1945-1989.; United States -- Foreign relations -- 1989-; Espionage -- United States -- History -- 20th century; Service des renseignements -- États-Unis -- Histoire -- 20e siècle.; Présidents -- États-Unis -- Histoire -- 20e siècle.; Espionnage -- États-Unis -- Histoire -- 20e siècle.; États-Unis -- Relations extérieures -- 1945-1989.; États-Unis -- Relations extérieures -- 1989-; TRUE CRIME -- Espionage; POLITICAL SCIENCE -- Political Freedom & Security -- Intelligence; POLITICAL SCIENCE -- Intelligence & Espionage; Espionage; Intelligence service; Diplomatic relations; Presidents; United States; Außenpolitik; CIA; Spionage; Presidenten; Since 1900; History